Effects of Different Doses of PMSG on Reproductive Performance in Chinese Holstein Dairy Cows - Shu-Bin Fu, Hua-Lin Zhang, Hasan Riaz, Sibtain Ahmad§, Xiao-Min Wang, Xiang Li, Guo-Hua Hua, Xiao-Ran Liu, Ai-Zhen Guo1 and Li-Guo Yang (Pakistan veterinary journal, 2013)
The current study was designed to evaluate the effect of different doses of pregnant mare serum gonadotropin (PMSG) on reproductive performance synchronized with prostaglandin F2α (PGF2α) in Chinese Holstein dairy cows. The study was conducted on one hundred cyclic dairy cows. Cows were equally divided into five treatment groups. Each group (n=20) was administered with an injection of PMSG (Serum Gonadotrophin for Injection, SanSheng Pharmaceutical, China) at dose rate of 2, 2.5, 3, 3.5, or 4 IU/kg BW, followed by an injection of PGF2α (Cloprostenol Sodium for Injection, SanSheng Pharmaceutical, China) 48 h later. Estrus was detected by a teaser bull three times daily after PGF2α administration. The cows were artificially inseminated 12 and 20 h after standing heat. On day 30 after artificial insemination, pregnancy rate was confirmed by transrectal ultrasonography while calving rate and multiple calvings were added up after successful parturition. There were no significant difference (P>0.05) in estrus response among all treatment groups. Similarly, interval from PMSG administration to estrus was decreased non-significantly (P>0.05) with the different doses of PMSG. Pregnancy rate was significantly lower (P<0.05) in the highest treatment group (4 IU/kg, 25%) than in low treatment groups (2 and 2.5 IU/kg, 71.4 and 66.7%). Calving rate was non-significant (P>0.05) among different regimens. The effects of PMSG dose on multiple calving was found to be statistically significant (P<0.05) and administration of 4 IU/kg PMSG resulted in 50% multiple births. The cows failed to get pregnant returned to estrus naturally. The interval from PMSG administration to first natural estrus was significantly higher (P<0.05) in high treatment groups (>2.5 IU/kg) than in the lowest treatment group (2 IU/kg), however, later pregnancy rate was non-significant (P>0.05) in all groups. In summary, PMSG administration could successfully induce estrus and improve fertility of a dairy herd. Furthermore, low doses of PMSG aid in quick return of non-pregnant cows to subsequent next estrus.